Electrocardiographic safety of repeated monthly dihydroartemisinin-piperaquine as a candidate for mass drug administration - Millat-Martínez, P.; Ila, R.; Laman, M.; Robinson, L.; Karunajeewa, H.; Abel, H.; Pulai, K.; Sanz, S.; Manning, L.; Moore, Brioni; Bassat, Q.; Mitjà, O. (American Society for Microbiology, 2018)
BACKGROUND: Mass drug administration (MDA) of sequential rounds of antimalarial drugs is being considered as a tool for malaria elimination. As an effective and long-acting antimalarial, Dihydroartemisinin-piperaquine (DHA/PQP) appears suitable as a candidate for MDA. However, absence of cardiac safety data following repeated administration hinders its use in the extended schedules proposed for MDA. METHODS: We conducted an interventional study in Lihir Island, Papua New Guinea, with healthy individuals aged 3 to 60 years who received a standard 3-day course of DHA/PQP on 3 consecutive months. Twelve-lead electrocardiography (ECG) readings were conducted pre-dose and 4h after the final dose of each month. The primary safety endpoint was QTc (using Fridericia's correction; QTcF) prolongation from baseline to 4h post-dosing. We compared the difference in prolongation between the third course post-dose and the first course post-dose. RESULTS: Of 84 enrolled participants, 69 (82%) completed all treatment courses and ECG measurements. The average increase in QTcF was 19.6 ms (SD 17.8) and 17.1 ms (SD 17.1) for the first-course and third-course post-dosing ECGs [risk difference -2.4 (95%CI - 6.9 to 2.1), p=0.285], respectively. We recorded QTcF prolongation >60 ms from baseline in 3 (4.3%) and 2 (2.9%) participants after the first course and third course (p=1.00), respectively. No participants had QTcF intervals >500 ms at any time point. CONCLUSIONS: Three consecutive monthly courses of DHA/PQP were as safe as a single course. The absence of cumulative cardiotoxicity with repeated dosing support the use of monthly DHA/PQP as part of malaria elimination strategies.